LIBERAL FEMINISM IN MOVIE NORTH COUNTRY DIRECTED BY NIKI CARO - Dwi Puji Hastuti; Deni Gunawan; Ria Andriani (LPPM Universitas Bina Sarana Informatika, 2018)
Women is still in lower position in every chace, especially in workplace. Equal rights is a must where every individual can get it. The purpose of this paper are explore about problems which happend there such as the reason why it can happend, impacts that main character and her co-worker as long as they work, and also obstacles in fighting for women’s right. This research uses descriptive qualitative method, data analysis is described by using words. Source date is taken from books and online resources, and others resource which completed this paper. This reasearch want to discuss about liberal feminism in this film, it is one of branch feminism theory which focused on fight for women’s right. As the result, Josey as the main character, she is bravely and clear woman who able speak out freedom for women and equal rights in workplace although almost the most worker there are men. Finally, with hard struggle and feel give up, she can do it.